2020
DOI: 10.1186/s13058-020-01309-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient treatment and outcome after breast cancer orbital and periorbital metastases: a comprehensive case series including analysis of lobular versus ductal tumor histology

Abstract: Background: Breast cancer is the most common malignancy to spread to the orbit and periorbit, and the invasive lobular carcinoma (ILC) histologic subtype of breast cancer has been reported to form these ophthalmic metastases (OM) more frequently than invasive ductal carcinomas (IDC). We herein report our single academic institution experience with breast cancer OM with respect to anatomical presentation, histology (lobular vs. ductal), treatment, and survival. Methods: We employed the natural language processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…An earlier study of Mathew et al found that after diagnosis of distant metastasis, there was no outcome difference between ILC and IDC, 38 while the study of Blohmer et al showed that, after diagnosis of the first distant metastasis, survival was much shorter for ILC patients than IDC patients. 39 The Cancer Genome Atlas (TCGA) research network recently published results of genomic characterization of 490 IDC and 127 ILC breast cancer cases. 2 , 40 As expected, ILC was prone to luminal A subtype, CDH1 mutations, and loss of E-cadherin by mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study of Mathew et al found that after diagnosis of distant metastasis, there was no outcome difference between ILC and IDC, 38 while the study of Blohmer et al showed that, after diagnosis of the first distant metastasis, survival was much shorter for ILC patients than IDC patients. 39 The Cancer Genome Atlas (TCGA) research network recently published results of genomic characterization of 490 IDC and 127 ILC breast cancer cases. 2 , 40 As expected, ILC was prone to luminal A subtype, CDH1 mutations, and loss of E-cadherin by mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of clear biological differences (e.g., sites of metastases), ILC is currently managed in the clinic in the same fashion as grade and stage-matched invasive breast cancer of no special type (IBC-NST). While prognosis over the short term is good, it is increasingly clear that ILC patients do worse than IBC-NST (grade-dependent) over time [ 3 , 4 ], and are more likely to metastasize to unusual sites, such as gynaecological and gastrointestinal organs, than IBC-NST [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous case reports of ILC seeding as orbital metastases appear to suggest these are more likely to arise from an ILC than other types, and in a sole example of a mixed ductal-lobular carcinoma, only the lobular component was found in the orbital metastasis (e.g. [19][20][21][22]).…”
Section: Introductionmentioning
confidence: 99%